Melatonina e AIB no enraizamento de estacas de cafeeiro arábica - Andrade, Francisco Hélio Alves de (2021)
Vegetative propagation enables the cloning of plants with high yield potential, resistant to biotic and abiotic stresses. Melatonin and indole-3-butyric acid (IBA) are molecules with the potential to stimulate root formation (RF), however, little is known about the effect of both on the activity of antioxidant enzymes, H2O2, phenols and alkaloids in the stages of development. rooting. The objective was to evaluate the impacts of melatonin and IBA application on root formation with enzymatic activity, H2O2 content, phenols and alkaloids. The present work is divided into two manuscripts, and in both, a completely randomized design with four replications was used. In the first manuscript, the following treatments were used: Control, 43 μM melatonin (M43), 215 μM melatonin (M215) and 7380 μM AIB (AIB), in the rooting phases, induction at 0 and 7 days after planting (DAP), initiation at 28 DAP and expansion at 47 and 76 DAP in arabica coffee cultivar Catuaí IAC-144. In the second manuscript, four treatments were tested (Control, melatonin at 21 μM (M21), M43 and IBA in the rooting phases, which are, induction at 0 and 7 DAP, initiation at 28 DAP and expansion at 47 and 69 DAP, used arabica coffee of the Mundo Novo cultivar. In both manuscripts, phytotechnical and biochemical parameters were performed. Article I: When cuttings were treated with M43, it was observed that H2O2 positively influenced at 0, 27 and 47 DAP for higher root dry matter weight (HRDMW). Furthermore, SOD, APX and CAT at 7 DAP correlated positively with HRDMW. At 28 DAP, SOD, POD and PPO also correlated with an increase in HRDMW. IBA application stimulated PPO at 0 DAP and APX and CAT correlated positively with HRDMW and negatively with the percentage of rooted cuttings (PRC). Biochemical evidence shows that increased enzymatic activity and H2O2 content at different rooting stages may be necessary for M43-induced root formation. The increase in enzymatic activity was involved in root formation and anticipation of rooting induced by the application of IBA. Article II: It was found that treatments M43 and AIB promoted higher PRC and trigonelline in induction and initiation, H2O2 in the initiation phase and total phenols in the induction phase. M43 increases the caffeine content in the induction and initiation of an associated RF. Caffeine, trigonelline, total phenols and H2O2 seem to be involved in the rooting of arabica coffee associated with the application of M43 and IBA.